2019
DOI: 10.1021/acsmedchemlett.9b00554
|View full text |Cite
|
Sign up to set email alerts
|

Missing Selectivity of Targeted 4β-Phorbol Prodrugs Expected to be Potential Chemotherapeutics

Abstract: Targeting cytotoxic 4β-phorbol esters toward cancer tissue was attempted by conjugating a 4β-pborbol derivative with substrates for the proteases prostate-specific antigen (PSA) and prostate-specific membrane antigen (PSMA) expressed in cancer tissue. The hydrophilic peptide moiety was hypothesized to prevent penetration of the prodrugs into cells and prevent interaction with PKC. Cleavage of the peptide in cancer tumors was envisioned to release lipophilic cytotoxins, which subsequently penetrate into cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Cell viability was determined by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) reduction assay, and cell membrane integrity using lactate dehydrogenase (LDH) release assay from cell culture media, as previously described (Tarvainen et al, 2020). In brief, the cells seeded onto 96-well plates (10 000 cells per well, in serum-supplemented media), were incubated with the compounds in normal cell culture medium for 24 h. The LDH assay was carried out with 50 µL samples of culture medium from each well.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Cell viability was determined by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) reduction assay, and cell membrane integrity using lactate dehydrogenase (LDH) release assay from cell culture media, as previously described (Tarvainen et al, 2020). In brief, the cells seeded onto 96-well plates (10 000 cells per well, in serum-supplemented media), were incubated with the compounds in normal cell culture medium for 24 h. The LDH assay was carried out with 50 µL samples of culture medium from each well.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Cytotoxic 4-phorbol esters were used to target cancerous tissues. The findings demonstrated that the phorbol prodrug effectively eliminated peptidase-positive and -negative cells and activated PKC [41]. Tsai et al studied the activation of PKC by phorbol esters using platelet aggregation as a model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results obtained in clinical phase II trial did not meet the expectations, and hence the drug was not marketed [ 58 ]. A major problem might be that the prodrug, despite its five negative charges on its peptide side chains, has been found to be able to penetrate cell membranes in benign cells, thereby causing unspecific toxicity [ 59 ].…”
Section: Prodrugsmentioning
confidence: 99%